The Impact of the Sharing Economy on Traditional Hospitality Models - Gasimba, Christopher (Journal of Modern Hospitality, 2024)
Purpose: The general objective of the study was to examine the impact of the sharing economy on traditional hospitality models. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the sharing economy on traditional hospitality models. Preliminary empirical review revealed that the sharing economy, exemplified by platforms like Airbnb, significantly disrupted traditional hospitality models, particularly affecting mid-tier and budget hotels with declines in revenue and occupancy. Luxury hotels, however, maintained resilience through brand reputation and superior services. It highlighted the importance of adaptive regulatory frameworks to ensure fair competition and consumer protection. The study recommended that traditional hotels innovate by embracing digital transformation and enhancing personalized experiences. These insights were deemed crucial for industry stakeholders to navigate the evolving hospitality landscape influenced by the sharing economy. Unique Contribution to Theory, Practice and Policy: The Disruptive Innovation Theory, Resource-Based View (RBV) Theory and Institutional Theory may be used to anchor future studies on sharing economy on traditional hospitality models. The study recommended several key actions for theory, practice, and policy to address the impact of the sharing economy on traditional hospitality models. Theoretically, it suggested expanding Disruptive Innovation and Institutional Theories to better understand market dynamics and regulatory influences. Practically, it advised traditional hotels to leverage their unique strengths, embrace digital transformation, form strategic partnerships, and innovate their service offerings to remain competitive. For policymakers, the study emphasized the need for adaptive regulatory frameworks to ensure fair competition and consumer protection. It also highlighted the importance of consumer education on the benefits and risks of different accommodation options. Future research directions included long-term impact studies, regional comparisons, and investigations into socio-cultural effects. Keywords: Sharing Economy, Traditional Hospitality Models, Disruptive Innovation Theory, Institutional Theory, Airbnb, Hotel Industry